2009
DOI: 10.1038/jes.2009.44
|View full text |Cite
|
Sign up to set email alerts
|

Assessing exposure to granite countertops—part 1: Radiation

Abstract: Humans are continuously exposed to low levels of ionizing radiation. Known sources include radon, soil, cosmic rays, medical treatment, food, and building products such as gypsum board and concrete. Little information exists about radiation emissions and associated doses from natural stone finish materials such as granite countertops in homes. To address this knowledge gap, gross radioactivity, g ray activity, and dose rate were determined for slabs of granite marketed for use as countertops. Annual effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 14 publications
1
26
0
2
Order By: Relevance
“…All flux calculations were conducted in the same manner as for the full-slab surface testing. In addition to the flux measurements, the radium-226 ( 226 Ra) activity of each corner sample was measured using gamma spectroscopy with a high-purity germanium detector, the details of which are described in Myatt et al (2009).…”
Section: Radon Flux Measurementsmentioning
confidence: 99%
“…All flux calculations were conducted in the same manner as for the full-slab surface testing. In addition to the flux measurements, the radium-226 ( 226 Ra) activity of each corner sample was measured using gamma spectroscopy with a high-purity germanium detector, the details of which are described in Myatt et al (2009).…”
Section: Radon Flux Measurementsmentioning
confidence: 99%
“…This represents an annual dose of about 7.1 mrem/y based on an exposure of 1 h/d for 365 d (5). Use of that type of granite as more than a kitchen countertop, for only 4 h a day, well exceeds 25% of an individual's annual effective dose of 100 mrem/y from a single manmade source.…”
Section: Granitementioning
confidence: 99%
“…Known radioisotopes found in granite include uranium and thorium; however, these two make up very small portions of granite (4,5). Radon gas ( 222 Rn) also is known to be a natural constituent of natural stones, such as granite, used as building materials (6).…”
mentioning
confidence: 99%
“…The lead shield contained two inner concentric cylinders of copper and cadmium to prevent interference X-rays by lead. The energy calibration of the HPGe spectrometer was carried out by using standard point sources ( Th with activities of 2120.37 and 1333.96 Bq, respectively and potassium chloride KCl solutions with activity 15.9 Bq [11], contained in the same cylindrical bottles with the same volume 250 cm 3 and having the same nature as the investigated samples. The standards and the samples were prepared with a uniform geometry.…”
Section: Experimental Methods For Gamma Spectroscopymentioning
confidence: 99%
“…Over the past decade, a number of studies have been reported on the activity concentrations of natural radionuclides for marble and granite samples obtained from different countries in the world [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%